Effects of chemical and organic fertilizer combinations on bioactive compounds and macro-micro nutrients in bell pepper (Capsicum annuum L.) fruits - Aytekin Ekincialp (Acta Scientiarum Polonorum: Hortorum Cultus)
This study aimed to identify strategies that are conducive  to both sustainable and high-yielding horticulture, with a focus on minimizing ecological damage by reducing dependence on chemical fertilizers. Sumo F1 bell pepper variety was used in an open-field experiment. The effect of three distinct fertilizer types (earthworm vermicompost Yaşa Tarım, organomineral fertilizer Hektaş, chemical fertilizer Gübretaş) and their respective combinations on biochemical, nutrient and color parameters of bell pepper fruits was evaluated. It was observed that biochemical values and nutrient levels were higher in treatments with vermicompost at 25, 50, 75 and 100% rates. The highest levels of organic acids (malic acid, succinic acid, fumaric acid, tartaric acid), polyphenols (chlorogenic acid, ferulic acid), total antioxidants, and nutrient elements (phosphorus, potassium, zinc) were obtained in treatments without chemical fertilizer. The results show that the use of organomineral fertilizer, especially vermicompost, plays a role in reducing the dependence on chemical fertilizer in bell pepper cultivation.